When handpicked successors of charismatic leaders prosper: the surprising success of Juan Manuel Santos in Colombia. Issue 6 (18th August 2022) - Andrews-Lee, Caitlin; Gamboa, Laura
ABSTRACT: Charismatic leaders, who loathe sharing power, often anoint sycophantic successors who fail to become powerful leaders in their own right. Curiously, however, Colombian President Juan Manuel Santos (2010–2018), the handpicked successor of Alvaro Uribe (2002–2010), became a remarkably effective leader who served two terms and oversaw Colombia's landmark 2016 peace agreement. We investigate this unlikely outcome and develop a novel theory to reveal a pathway through which some handpicked successors of charismatic leaders can establish independent authority. We argue that success is more likely when the successor breaks away from the predecessor. However, doing so requires the successor to engage in a sequential and highly strategic process we label tightrope walking, in which the new leader gains the predecessor's endorsement to win office, expands his/her coalition by incorporating new allies from outside the predecessor's base, and reforms the predecessor's unsustainable policies and narrative. To substantiate our theory, we trace how Santos moved through each stage of the tightrope-walking process and ultimately broke from Uribe to achieve independent authority. The results suggest a rare but important mechanism through which charismatic movements can be challenged from the inside out, curtailing or reversing democratic erosion.